Assessment of ghee adulterated with oils and fats in Bangladesh - Ahmed, Shabbir; Hamid, Mohammod Abdul; Rahman, Md Morshedur (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed at determining the existence of oils and fats in ghee manufactured in Bangladesh and to validate the nature of the impurity. Materials and Methods: In this study, a ghee sample was prepared in the laboratory by following standard methods and was used as a control sample. On the other hand, 19 ghee samples, including five branded samples (B1–B5), and 14 local samples (L1–L14) were collected from different manufacturers. The ghee samples were assessed for fat composition, Reichert Meissl (RM), saponification, Polenske, acid, Kirschner, and butyro refractometer (BR) values. To validate the ghee samples, vegetable oils and body fats were mixed in different ratios and then analyzed. Results: All the branded samples contained more than 99.5% fat, but only three local samples showed more than 97% fat. Admixing of soybean oil and coconut oil in different ratios showed the RM value from 1.57 ± 0.09 to 4.14 ± 0.21, whereas incorporation of hydrogenated vegetable oils and tallow showed 6.36 ± 0.03 to 14.10 ± 0.14. Nine local samples revealed RM values similar to external fat admixed samples. B2, B4, B5, L2–L8, and L10–L14 samples’ saponification values differed from the standard limits. Polenske, acid, Kirschner values and BR reading for L4, L6, L7, L8, L10, L12, L13, and L14 showed the worst results. All values varied significantly (p < 0.01). Conclusion: Local samples, L4, L6, L7, L8, L10, L12, L13, and L14, were assumed to be adulterated with external oils and fats. The quality of local ghee is questionable, as the samples contained more than 8% moisture, whereas pure ghee had less than 0.5% moisture. J. Adv. Vet. Anim. Res., 7(4): 678-684, Dec 2020 http://doi.org/10.5455/javar.2020.g467